RELATIONS OF PATTERN CURRENT AND SEDIMENT CHARACTERISTICS IN SASAK BEACH WEST PASAMAN REGENCY PROVINCE OF WEST SUMATERA - Annisa Al-Qhoshashi; Rifardi Rifardi; Aras Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in Mei 2018, to analysis relations of pattern current and sediment characteristics in Sasak Beach. The sediment samples were taken from four stations and anylised at Oceanography Laboratory Fisheries and Marine Faculty University of Riau. The result of the research, station I shows the dominant fraction is sandy mud under the influence of current velocity 0,10 m/s at high tide and 0,5 m/s at low tide. In station II shows the dominant fraction is mud sandy under the influence of current velocity 0,7 m/s at high tide and 1 m/s at low tide. In station III shows the dominant fraction is sandy gravel under the influence of current velocity 0,3 m/s at high tide and 0,8 m/s at low tide. In station IV shows the dominant fraction is sandy gravel under the influence of current velocity 0,8 m/s at high tide and 1,2 m/s at low tide. Keywords: Current, Sediment, Sasak Beach